Sustainable Marine and Coastal Tourism: A Catalyst for Blue Economic Expansion in Sri Lanka - B.S, Galdolage; E.A, Ekanayake; Al-Daoud, Khaleel Ibrahim; ., Vasudevan A; Wenchang, Chen; Hunitie, Mohammad Faleh Ahmmad; Mohammad, Suleiman Ibrahim Shelash (Journal of Ecohumanism, 2024)
Sri Lanka is concentrating on growing its blue economy, which entails the sustainable use of marine resources to enhance economic advancement, livelihoods, and job opportunities while safeguarding the ocean ecosystem. The major data gathering approach for the qualitative research was key-person interviews, which were then processed using theme analysis. According to the report, the country’s geographical location, marine and coastal tourist product diversification, and human resource availability are all potential growth opportunities. Limited infrastructure, lack of sectorial collaboration, and inadequate private sector involvement are some of the obstacles identified in expanding the marine and coastal tourism sector. Public-private partnerships, industry infrastructure development, sectorial collaboration and port development are possible solutions to these challenges. Sri Lanka has a lot of potential for underwater and coastal tourism. The blue economy can significantly contribute to the country’s economic growth if it implements the right strategies. Future investments in marine and coastal tourism can be influenced by the findings of this study.